TRAFFIC FLOW AND SAFETY ANALYSIS AT URBAN INTERSECTION: SELECTED STUDY CASE - Ahmad Raqib Ab. Ghani (2026)
In the bustling context of urban planning, this study aimed to address the primary objective of identifying operational failures at signalized intersections, with a specific focus on the chaotic interplay of mixed traffic. The findings painted a stark picture of the limitations inherent in current traffic models. It was observed that the sheer volume of motorcycles disrupted standard "gap acceptance" behaviors, creating unique "dilemma zones" that traditional Highway Capacity Manual (HCM) methodologies overlook. The data revealed that drivers frequently misjudged the approach speed of smaller vehicles during permissive phases, leading to critical conflicts that statistical averages often fail to capture. The contribution of this work lies in its translation of observed chaos into actionable engineering data. By establishing new saturation flow baselines and identifying specific geometric flaws, the study offers more than a summary of traffic counts; it proposes a recalibrated framework for safety audits. Ultimately, it advocates for a specific shift from permissive to protected signal phasing, providing a technical roadmap to reduce accident severity and harmonize the flow of diverse vehicle types in developing urban centers.